Pollen tube growth of Paeonia tenuifolia L. (Paeoniaceae) in vitro and in vivo - Dane, Feruzan; Ekici, Nuran (Bangladesh Journal of Botany, 2011)
In vitro and in vivo studies on pollen germination of Paeonia tenuifolia L. (Paeoniaceae) revealed that pollen grains are shed at two-celled stage. Normal and abnormal pollens were observed. Pollen viability was recorded between 55 and 75%. In vitro studies revealed 85% germination and usually the germination was monosphonic. Some pollen tubes with swollen tube tip and undulations were found. Styles and stigma were found to contain many pollen tubes 24 hrs after pollination. Key words: Paeonia tenuifolia; Pollen tube; In vitro growth; In vivo growth DOI: http://dx.doi.org/10.3329/bjb.v40i1.8003 Bangladesh J. Bot. 40(1): 93-95, 2011 (June)